Ethylene sustained-release material as well as preparation method and application thereof

By using a combination of chitosan quaternary ammonium salt, ethylene, porous starch, calcium chloride and sodium alginate, the problems of poor sustained release effect and environmental pollution in the existing materials in humidity environments are solved. Stable and quantitative ethylene sustained release and biodegradability of the material are achieved.

CN119453291APending Publication Date: 2025-02-18SHAANXI NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411372531.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing ethylene sustained-release materials have poor controllable sustained-release effects in humidity environments, and the raw materials are difficult to degrade, resulting in environmental pollution, and the preparation method is complicated and inconvenient to use.

Method used

The combination of chitosan quaternary ammonium salt, ethylene liporidium, porous starch, calcium chloride and sodium alginate was prepared by ultrasonic and stirring to achieve stable sustained release in a humidity environment.

Benefits of technology

The stable sustained release of ethylene is achieved in a humidity environment, which has good biodegradability, avoids environmental pollution, is simple in preparation, is easy to store and use, and can achieve quantitative sustained release of ethylene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119453291A_ABST
    Figure CN119453291A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sustained-release materials, and particularly relates to an ethylene sustained-release material and a preparation method and application thereof.The ethylene sustained-release material comprises chitosan quaternary ammonium salt, an ethephon solution, porous starch, calcium chloride and sodium alginate; the mass ratio of the chitosan quaternary ammonium salt to the ethephon to the porous starch to the calcium chloride to the sodium alginate is (0.3-0.6): (0.01-0.15): (8-12): (7-15): 1. The ethylene sustained-release material formed by the invention has a very good sustained-release effect on ethylene in a humidity environment, also has very good biodegradability, and avoids pollution to the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sustained-release materials, and in particular relates to an ethylene sustained-release material and a preparation method and application thereof. Background Art

[0002] Ethylene slow-release agent is a plant ripening agent, and its main function is to ripen fruits. Put the ethylene slow-release agent and fruits in a sealed container, and then maintain a suitable temperature. After about 3-5 days, the fruits will reach a state of being about to mature.

[0003] The Chinese invention patent with publication number CN104145987A discloses the preparation and application of an ethephon controlled sustained-release material. The material is a composite film made of an alkaline polymer and ethephon. The ethephon controlled sustained-release material can be used in an air medium or a buffer solution, but the sustained-release rate is affected by air humidity, ethephon content and buffer solution value.

[0004] Although the disclosed sustained-release materials can achieve controlled sustained-release of ethephon, the following problems exist: first, the controlled sustained-release effect of existing sustained-release materials in a humid environment is still poor; second, the raw materials required for existing sustained-release materials cannot be effectively degraded, and are likely to cause ecological environmental pollution after use; in addition, most of the existing sustained-release materials exist in the form of films, which makes the sustained-release materials have a single mode in the subsequent application process, the use method is not convenient enough, and the preparation method is complicated, which increases the preparation cost. Summary of the invention

[0005] In view of the technical problems that the existing sustained-release materials still have poor controllable sustained-release effect in a humid environment and are prone to pollution, the present invention provides an ethylene sustained-release material and a preparation method and application thereof.

[0006] The invention utilizes chitosan quaternary ammonium salt, ethephon solution, porous starch, calcium chloride and sodium alginate to form an ethylene slow-release material, which has a good slow-release effect on ethylene in a humid environment and has good biodegradability, thus avoiding environmental pollution.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] An ethylene sustained-release material comprises chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate; the mass ratio of the chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate is (0.3-0.6):(0.01-0.15):(8-12):(7-15):1.

[0009] It is further defined that the mass ratio of the chitosan quaternary ammonium salt, the ethephon solution, the porous starch, the calcium chloride and the sodium alginate is 0.5:(0.06-0.12):10:11:1.

[0010] The preparation method of the ethylene sustained-release material as described above comprises the following steps:

[0011] S1. Prepare chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate according to the mass ratio;

[0012] S2, dissolving calcium chloride in water, adding chitosan quaternary ammonium salt, and subjecting to ultrasonication and stirring to obtain a mixed solution A;

[0013] S3, dissolving ethephon in water to obtain an ethephon solution, and then dissolving sodium alginate in the ethephon solution until it is completely dissolved to form a stable and uniform system; then adding porous starch, homogenizing and degassing to obtain a mixed solution B;

[0014] S4. Add the mixed solution B to the mixed solution A at a uniform speed, stir evenly, let stand, separate, obtain gel beads, and dry to obtain the granular target product.

[0015] It is further defined that in step S2, the frequency of ultrasound is 100 Hz to 160 Hz, and the time of ultrasound is 5 min to 10 min; the speed of stirring is 2000 r / min to 2200 r / min, and the time of stirring is 15 min to 25 min.

[0016] It is further defined that in step S4, the standing time is 3 min to 5 min, and the drying is performed at 55° C. to 70° C. for 7 h to 8 h.

[0017] It is further defined that the diameter of the target product is 3 mm to 5 mm.

[0018] The ethylene slow-release material is used for delaying the ethylene release rate.

[0019] The ethylene slow-release material is used in the controllable ripening of kiwi fruit.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention forms an ethylene sustained-release material by using chitosan quaternary ammonium salt, ethephon, sodium alginate, porous starch and calcium chloride, which has a good stable sustained-release effect on ethylene under a humid environment; it also has good biodegradability and avoids pollution to the environment.

[0022] 2. The ethylene sustained-release material provided by the present invention is granular, has high porosity and high specific surface area, can greatly slow down the release of ethylene, can continuously release for up to 120 hours, and is sensitive to environmental humidity.

[0023] 3. The raw materials used in the present invention, such as chitosan quaternary ammonium salt, ethephon, sodium alginate, porous starch and calcium chloride, have good biodegradability, will not cause ecological pollution, and the sustained-release material is more environmentally friendly; it also has good hygroscopicity, solubility and gelling properties.

[0024] 4. The ethylene sustained-release material prepared by the present invention has good stability; and the formed granular material is not only easy to store, but also can be used immediately after opening; moreover, the granular material has diversified usage modes and is more convenient.

[0025] 5. The ethylene slow-release material provided by the present invention can also realize the quantitative slow-release of ethylene, and can play a good role in quantitative ripening of kiwifruit when used in kiwifruit.

[0026] 6. When preparing ethylene sustained-release materials, the present invention has a simple preparation method and mild conditions, thereby reducing the preparation cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Figure 2 is a powdered ethylene sustained-release material prepared by the present invention;

[0028] Figure 2 FIG. 1 is a diagram of a film-like ethylene sustained-release material prepared by the present invention;

[0029] Figure 3 FIG. 1 is a diagram of a granular ethylene sustained-release material prepared by the present invention;

[0030] Figure 4 This is a microscopic morphology of granular ethylene sustained-release material;

[0031] Figure 5 This is the Fourier infrared characterization result of granular ethylene sustained-release material;

[0032] Figure 6 It is the result of ethylene slow-release rate of powdered ethylene slow-release material;

[0033] Figure 7 It is the result of ethylene slow-release rate of the film-like ethylene slow-release material;

[0034] Figure 8 It is the result of ethylene slow-release rate of granular ethylene slow-release material;

[0035] Fig. 9 Comparison of ethylene release from granular ethylene slow-release materials at different ethephon concentrations;

[0036] Fig.10 Comparison of ethylene release rates of granular ethylene slow-release materials at different ethephon concentrations;

[0037] Fig.11 This is the weight-bearing result of the granular ethylene slow-release material;

[0038] Fig.12 The results of the effect of granular ethylene slow-release material on the hardness of kiwi fruit;

[0039] Fig.13 The results of soluble solid solution of granular ethylene slow-release material on kiwi fruit;

[0040] Fig.14 The titratable acid results for kiwifruit from granular ethylene slow-release materials;

[0041] Fig.15 This is the result of ethylene release of kiwifruit by granular ethylene slow-release material;

[0042] Fig.16 Comparison of the swelling capacity of different ethylene sustained-release materials;

[0043] Fig.17 Comparison of X-ray diffraction results of different ethylene sustained-release materials;

[0044] Fig.18 The ethylene release kinetics under different relative humidity environments (15%, 50%, 85%). DETAILED DESCRIPTION

[0045] The technical solution protected by the present invention is now described in detail. However, it is obvious that the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the described embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0046] The invention provides an ethylene sustained-release material, which comprises chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate.

[0047] In the present invention, the mass ratio of chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate is (0.3-0.6): (0.01-0.15): (8-12): (7-15): 1.

[0048] Preferably, the mass ratio of chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate is 0.3:0.01:8:7:1.

[0049] Preferably, the mass ratio of chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate is 0.6:0.15:12:15:1.

[0050] Preferably, the mass ratio of chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate is 0.45:0.1:10:12:1.

[0051] More preferably, the mass ratio of chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate is 0.5:0.06:10:11:1.

[0052] More preferably, the mass ratio of chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate is 0.5:0.12:10:11:1.

[0053] The present invention also provides a method for preparing an ethylene sustained-release material, comprising the following steps:

[0054] S1. Weigh chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate respectively according to the above mass ratio.

[0055] S2. Dissolve calcium chloride in water, add chitosan quaternary ammonium salt, and obtain a mixed solution A by ultrasonication and stirring.

[0056] Preferably, in this step, the frequency of ultrasound is 100 Hz to 160 Hz, and the time of ultrasound is 5 min to 10 min; the speed of stirring is 2000 r / min to 2200 r / min, and the time of stirring is 15 min to 25 min.

[0057] Preferably, the amount of water used in this step is 500 mL, which is used to mix the calcium chloride and chitosan quaternary ammonium salt evenly and mix them evenly with the subsequent solution B.

[0058] S3. Ethephon is dissolved in water to obtain an ethephon solution, and then sodium alginate is dissolved in the ethephon solution until it is completely dissolved to form a stable and uniform system; porous starch is then added, and a mixed solution B is obtained after homogenization and degassing.

[0059] Preferably, the amount of water used in this step is 100 mL, and its function is to mix the ethephon, sodium alginate and porous starch evenly, and to mix them evenly with solution A.

[0060] S4. Add the mixed solution B to the mixed solution A at a uniform speed, stir evenly, let stand, separate, obtain gel beads, and dry to obtain the granular target product.

[0061] Preferably, in this step, the standing time is 3 to 5 minutes, and the drying is carried out at 55° C. to 70° C. for 7 hours to 8 hours; and the particle diameter of the target product is 3 mm to 5 mm.

[0062] The ethylene slow-release material provided by the present invention has good hygroscopicity, solubility and gelling property, has good controllable slow-release property in a humid environment, effectively delays the ethylene release rate, and can be well used in kiwifruit ripening.

[0063] The preparation method and performance of the present invention are described below through several groups of specific examples.

[0064] It should be noted that, unless otherwise specified, the reagents, raw materials, etc. used in the following examples are all commercially available products.

[0065] It should be noted that, unless otherwise specified, the operations used in the following embodiments are all conventional operations in the art, such as dissolving, stirring, and crushing.

[0066] Example 1

[0067] In this embodiment, the ethylene sustained-release material includes chitosan quaternary ammonium salt (HACC), sodium alginate, ethephon, calcium chloride and porous starch.

[0068] In this embodiment, the mass ratio of chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate is 0.5:0.05:10:11:1.

[0069] The method for preparing the ethylene sustained-release material provided in this embodiment comprises the following steps:

[0070] S1. Dissolve 11 g of calcium chloride in 500 mL of water to prepare a 0.2 mol / L calcium chloride solution; then take 0.5 g of chitosan quaternary ammonium salt (HACC) and dissolve it in the calcium chloride solution, ultrasonicate, magnetically stir, control the speed at 400 r / min at room temperature, and mix well to obtain a mixed solution A.

[0071] S2, take 0.12g of ethephon and dissolve it in 100mL of water to form an ethephon solution; take 1g of sodium alginate and dissolve it in the ethephon solution, stir it magnetically until it is completely dissolved into a stable and uniform system; continue to add 10g of porous starch, homogenize, and degas to obtain a mixed solution B;

[0072] S3. Use a needle to uniformly drip the mixed solution B of step S2 into the mixed solution A of step S1, slowly stir after dripping, let stand for 5 minutes, filter and separate, put the obtained gel beads into an oven, and dry them at 60° C. for 7 hours to obtain a granular ethylene sustained-release material.

[0073] The ethylene sustained-release material prepared in this embodiment has an appearance as follows Figure 1 As shown, solid particles with a diameter of 3mm-5mm.

[0074] Example 2

[0075] In this embodiment, the ethylene sustained-release material includes chitosan quaternary ammonium salt (HACC), sodium alginate, ethephon, calcium chloride and porous starch.

[0076] In this embodiment, the mass ratio of chitosan quaternary ammonium salt, ethephon solution, porous starch, calcium chloride and sodium alginate is 0.5:0.06:10:11:1.

[0077] The method for preparing the ethylene sustained-release material provided in this embodiment comprises the following steps:

[0078] S1. Dissolve 11 g of calcium chloride in 500 mL of water to prepare a 0.2 mol / L calcium chloride solution; then take 0.5 g of chitosan quaternary ammonium salt (HACC) and dissolve it in the calcium chloride solution, ultrasonicate, magnetically stir, control the speed at 400 r / min at room temperature, and mix well to obtain a mixed solution A.

[0079] S2, take 0.06g of ethephon and dissolve it in 100mL of water to form an ethephon solution; take 1g of sodium alginate and dissolve it in the ethephon solution, stir it magnetically until it is completely dissolved into a stable and uniform system; continue to add 10g of porous starch, homogenize, and degas to obtain a mixed solution B;

[0080] S3. Use a needle to uniformly drip the mixed solution B of step S2 into the mixed solution A of step S1, slowly stir after dripping, let stand for 5 minutes, filter and separate, put the obtained gel beads into an oven, and dry them at 60° C. for 7 hours to obtain a granular ethylene sustained-release material.

[0081] The ethylene sustained-release material prepared in this embodiment has an appearance as follows Figure 1 As shown, the solid particles are 3-5 mm in diameter.

[0082] Comparative Example 1

[0083] The preparation method of the ethylene sustained-release material provided in this comparative example comprises the following steps:

[0084] S1, take 0.12g of ethephon and dissolve it in 100mL of water to form an ethephon solution, take 5g of chitosan quaternary ammonium salt and dissolve it in the ethephon solution, and stir magnetically until it is completely dissolved into a stable and uniform system;

[0085] S2. After the bubbles in the stable and uniform system are eliminated, pour it onto a flat plate to form a film, and peel it off after drying for 2 hours to obtain a film-like ethylene sustained-release material.

[0086] In this comparative example, the appearance of the ethylene sustained-release material is as follows: Figure 2 As shown, it is a solid film with uniform thickness.

[0087] Comparative Example 2

[0088] The preparation method of the ethylene sustained-release material provided in this comparative example comprises the following steps:

[0089] S1. Take 0.12g of ethephon and dissolve it in 100mL of water to form an ethephon solution. Take 5g of chitosan quaternary ammonium salt and dissolve it in the ethephon solution. Stir magnetically until it is completely dissolved into a stable and uniform system.

[0090] S2. Add 10 g of porous starch to the stable and uniform system, homogenize, degas, spread it in a culture dish, dry it for 3 hours, and grind it to obtain a powdered ethylene sustained-release material.

[0091] In this comparative example, the appearance of the ethylene sustained-release material is as follows: Figure 3 As shown, it is a solid powder.

[0092] Comparative Example 3

[0093] The preparation method of the ethylene sustained-release material provided in this comparative example comprises the following steps:

[0094] S1. Dissolve 11 g of calcium chloride in 500 mL of water to prepare a 0.2 mol / L calcium chloride solution; stir the mixture by ultrasound, magnetic stirring, and control the rotation speed to 400 r / min at room temperature to obtain a mixed solution A after mixing evenly;

[0095] S2, take 0.12g of ethephon and dissolve it in 100mL of water to form an ethephon solution; take 1g of sodium alginate and dissolve it in the ethephon solution, stir it magnetically until it is completely dissolved into a stable and uniform system; continue to add 10g of porous starch, homogenize, and degas to obtain a mixed solution B;

[0096] S3. Use a needle to uniformly drip the mixed solution B of step S2 into the mixed solution A of step S1, slowly stir after dripping, let stand for 5 minutes, filter and separate, put the obtained gel beads into an oven, and dry them at 60° C. for 8 hours to obtain ethylene sustained-release material.

[0097] Comparative Example 4

[0098] The preparation method of the ethylene sustained-release material provided in this comparative example comprises the following steps:

[0099] S1. Dissolve 11 g of calcium chloride in 500 mL of water to prepare a 0.2 mol / L calcium chloride solution; stir the mixture by ultrasound, magnetic stirring, and control the rotation speed to 400 r / min at room temperature to obtain a mixed solution A after mixing evenly;

[0100] S2, take 0.06g of ethephon and dissolve it in 100mL of water to form an ethephon solution; take 1g of sodium alginate and dissolve it in the ethephon solution, stir it magnetically until it is completely dissolved into a stable and uniform system; continue to add 10g of porous starch, homogenize, and degas to obtain a mixed solution B;

[0101] S3. Use a needle to uniformly drip the mixed solution B of step S2 into the mixed solution A of step S1, slowly stir after dripping, let stand for 5 minutes, filter and separate, put the obtained gel beads into an oven, and dry them at 60° C. for 8 hours to obtain ethylene sustained-release material.

[0102] The performance of the ethylene sustained-release materials prepared in the above examples and comparative examples was characterized by the following tests.

[0103] Test 1: Morphology

[0104] Test sample: the ethylene sustained-release material of Example 1.

[0105] Test method: The surface microstructure of the above materials was characterized by using a tungsten filament scanning electron microscope with an acceleration voltage of 10KV and a magnification of 5.00K. The results are as follows: Figure 4 shown.

[0106] from Figure 4 It can be seen that after the material is magnified, it can be seen that the material is composed of porous starch macromolecular particles, each of which is rich in many pores from the inside to the outside. The pores can embed ethephon crystals, providing a basis for the material's sustained release ability.

[0107] Test 2: Infrared

[0108] Test samples: ethylene sustained-release materials of Example 1, Example 2, Comparative Example 3 and Comparative Example 4, marked as 350H, 700H, 350 and 700, respectively.

[0109] This experiment also set up a CK group: the ethylene sustained-release material includes chitosan quaternary ammonium salt (HACC), sodium alginate, calcium chloride and porous starch. The mass ratio of each raw material and the preparation method refer to Example 1.

[0110] Test method: Take 2 mg of sample and grind it into fine powder in an agate mortar, add appropriate amount of dry potassium bromide powder, mix well, put it into a mold, and press it into tablets on a tablet press. Put the flake sample into the sample chamber, adjust the infrared spectrometer parameters, and scan the frequency range of 4000-500cm -1 , resolution 4cm -1 , the number of scans is 16; the results are as follows Figure 5 shown.

[0111] from Figure 5 It can be seen that there is no significant change in the vibration peak positions of the corresponding wavelengths of the five groups of materials, indicating that the addition of ethephon did not change the internal chemical bonds of porous starch. -1 The broad absorption peak at 1617 cm -1 There is C=O double bond stretching vibration at 1414cm -1 and 1347cm -1 The absorption peak at 1148 cm is mainly caused by CH stretching vibration. -1 、1071cm -1 、1002cm -1and 929cm -1 The absorption peaks at 1022 cm -1 and 1047cm -1 The wavelengths of 350, 700, 350H and 700H represent the amorphous region and crystalline region of porous starch, respectively. -1 、1071cm -1 and 1002cm -1 The absorption peak was enhanced, indicating that there was a physical interaction between ethephon and porous starch molecules. The groups of the porous starch itself in the other four groups were not destroyed compared with the CK group, proving that ethephon was successfully encapsulated by PS.

[0112] Experiment 3: Ethylene release rate of materials with different shapes

[0113] The main purpose of this test is to monitor the ethylene release rate by gas chromatography.

[0114] Test samples: ethylene sustained-release materials prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0115] Test method: Take 4g of sample and place it in a sample bottle with a gas outlet on the bottle cap. Open the bottle cap and place it in an environment with a relative humidity of 85% and a temperature of 21°C for 6h. Then use a fan to blow out the residual ethylene gas in the bottle, tighten the bottle cap, and place it for 1h to collect ethylene gas. Finally, inject 1ml into Shimadzu gas chromatograph (Shimadzu gas chromatograph GC 2010-Pro hydrogen flame ionization detector (FID), carrier gas N2 flow rate 18mL / min, fuel gas H2 flow rate 21mL / min, combustion gas air flow rate 150mL / min. Injector temperature 120°C, chromatographic column temperature 60°C, detector temperature 200°C), obtain the peak area, and obtain the concentration of ethylene gas in the bottle based on the peak area and the ethylene gas standard curve, and obtain the ethylene release per gram of sample per minute; unit: (μL / g﹒min), test results refer to Figure 6 , Figure 7 and Figure 8 .

[0116] See also Figure 6 , Figure 7 and Figure 8The granular ethylene slow-release material prepared in Example 1 has the best ethylene release effect, and its release level is maintained at about 0.2μL / g﹒min; while the powdered ethylene slow-release material prepared in Comparative Example 2 and the film-like ethylene slow-release material prepared in Comparative Example 1 have extremely unstable release levels, and the ethylene release amount fluctuates greatly. This is because the film-like ethylene slow-release material contains only ethephon and HACC in its raw materials, and HACC has strong hygroscopicity, so the ethylene release rate is very high at the beginning, and then it drops rapidly; while the raw materials of the powdered ethylene slow-release material are added with ethephon porous starch and sodium alginate, and compared with HACC, the hygroscopicity of sodium alginate is relatively weak, so the initial ethylene release rate of the material is not high, and the ethylene release rate is still not stable enough; the granular ethylene slow-release material uses the sodium alginate-calcium ion crosslinking method to embed the porous starch-ethephon mixture to form slow-release beads, and then uses HACC as the material shell, so that the ethephon in the spherical particles is gradually decomposed from the inside to the outside to release ethylene, thereby having the characteristic of stable ethylene release.

[0117] Test 4: Total Ethylene Release

[0118] This test mainly monitors the ethylene release rate through gas chromatography and calculates the total amount of ethylene released.

[0119] Test samples: ethylene sustained-release materials prepared in Example 1 and Example 2, marked as 350H and 700H respectively.

[0120] Test method: Weigh 1g of sample into the headspace bottle, add 1ml of aqueous solution into the bottle, seal it, wait for 72 hours, inject 1ml into the gas chromatograph, and analyze the ethylene gas content in the headspace bottle. At the same time, calculate the ethylene release per gram of sample according to the dry weight ratio of ethephon in the material, the ethephon decomposition reaction equation and the standard atmospheric pressure. The results are as follows: Fig. 9 shown.

[0121] See also Fig. 9 The ethylene sustained-release material prepared in Example 1 (350H group) has a total ethylene release of 1552.37 μL / g, and the ethylene sustained-release material prepared in Example 2 (700 group) has a total ethylene release of 746 μL / g. The release amount of Example 2 is less than that of Example 1. This is because the ethephon solution formed in the preparation of Example 2 has a lower concentration, and the pH of the ethephon solution is greater than 4, so that part of the ethephon is decomposed in advance, resulting in a lower release amount. The ethephon solution formed in the preparation of Example 1 has a higher concentration, and ethylene will not be released in advance, so that the ethephon can be completely embedded in the porous starch, thereby increasing the total ethylene release.

[0122] Test 5: Ethylene release rate

[0123] The main purpose of this test is to monitor the ethylene release rate by gas chromatography.

[0124] Test samples: ethylene sustained-release materials prepared in Example 1 and Example 2, respectively denoted as 350H group and 700H group.

[0125] Test method: Take 4g of sample and place it in a sample bottle with a gas outlet on the bottle cap. Open the bottle cap and place it in an environment with a relative humidity of 85% and a temperature of 21°C for 6 hours. Then use a fan to blow away the residual ethylene gas in the bottle, tighten the bottle cap, and place it for 1 hour to collect ethylene gas. Finally, inject 1ml into Shimadzu gas chromatograph (Shimadzu gas chromatograph GC 2010-Pro hydrogen flame ionization detector (FID), carrier gas N2 flow rate is 18mL / min, fuel gas H2 flow rate is 21mL / min, combustion gas air flow rate is 150mL / min. Injector temperature is 120°C, chromatographic column temperature is 60°C, and detector temperature is 200°C) to obtain the peak area. According to the peak area and the ethylene gas standard curve, the concentration of ethylene gas in the bottle is obtained, and the ethylene release per gram of material per minute is obtained; unit: (μL / g﹒min). The test results are as follows Fig.10 As shown, (a) is a 350H group and (b) is a 700H group.

[0126] from Fig.10 It can be seen that the ethylene release level of the ethylene slow-release materials prepared in Example 1 and Example 2 is maintained at 0.5-2μL / g﹒min, and can be continuously released for up to 120h, because in the preparation process of the ethylene slow-release material, ethephon is embedded in porous starch and then cross-linked with sodium alginate and calcium ions to form particles with a diameter of about 3mm-5mm after drying. This provides conditions for the slow release of ethylene. At the same time, since chitosan quaternary ammonium salt has good water absorption and good slow-release performance, and the aqueous solution is alkaline, the slow release of ethylene can be further guaranteed.

[0127] Test 6: Determination of material moisture absorption rate

[0128] Test samples: the ethylene slow-release material of Example 1, the ethylene slow-release material of Example 2, the ethylene slow-release material of Comparative Example 3 and the ethylene slow-release material of Comparative Example 4, which are denoted as 350H, 700H, 350 and 700 respectively.

[0129] Test method: Place the sample in an environment with a relative humidity of 85% and a temperature of 21°C, and take it out and weigh it every 6 hours; the test results are as follows: Fig.11 shown.

[0130] from Fig.11It can be seen that there is no significant difference in the moisture absorption rate of the four samples, and the moisture absorption amount shows an overall trend of uniform increase. Within 0 to 36 hours, the moisture absorption rate of the bead shell using chitosan quaternary ammonium salt is slower than that of the unused group. This is because the hygroscopicity of sodium alginate is stronger than that of chitosan quaternary ammonium salt. Therefore, when there is no chitosan quaternary ammonium salt shell coating, the material has strong hygroscopicity in the early stage, as shown in the figure. However, within 36 to 120 hours, the moisture absorption rate of the bead shell using chitosan quaternary ammonium salt is faster than that of the unused group. This is because after the chitosan quaternary ammonium salt shell is saturated with moisture, the internal sodium alginate begins to absorb water vapor and has a stronger hygroscopic capacity. In summary, the addition of chitosan quaternary ammonium salt can stabilize the moisture absorption rate of the material, provide conditions for the hydrolysis of ethephon and the stable release of ethylene, and enable it to release ethylene evenly and stably under an environment with a relative humidity of about 85%.

[0131] Experiment 7: Kiwifruit treatment

[0132] This experiment mainly focuses on the application of ethylene slow-release materials on kiwi fruit.

[0133] The specific method for ripening and preserving kiwifruit is as follows: select 160 kiwifruits of uniform size and without damage, divide them into four groups, and randomly divide the 40 kiwifruits in each group into two parts, and place them in a ripening box (volume of about 26L), with 20 kiwifruits in each box, two boxes in each group, and a total of four groups.

[0134] There are two boxes in each group, one of which is a control group (CK) that is subjected to natural ripening treatment; the other box is an ethylene slow-release agent treatment group (E2K) with 20g of the ethylene slow-release material of Example 1, specifically, 20g of ethylene slow-release agent is placed in the air-permeable interlayer of the inner wall of the ripening box.

[0135] The four groups were tested on four performance indicators, including hardness test, soluble solid test, titratable acid test, and ethylene release test.

[0136] 7.1 Hardness

[0137] The test method is to cut off a small piece of thin peel (about 1mm thick) at three locations with equal distances along the equator of the kiwi fruit, and use a GY-1 fruit hardness tester to measure the hardness of the flesh at each location. Fig.12 shown.

[0138] from Fig.12 It can be seen that: with the increase of storage time, the hardness of the ethylene slow-release agent treatment group was significantly lower than that of the CK group. The ethylene slow-release agent can significantly ripen kiwifruit within 3 days and reduce its hardness. The high concentration of ethylene slow-release agent treatment can make the kiwifruit hardness decrease faster.

[0139] 7.2 Soluble solid solution

[0140] The test method is: take 5.0g of kiwi fruit sample, put it into a mortar and crush it, centrifuge it at 4000r / min for 10min or filter it and take the juice for determination. Use a dropper to absorb the sample liquid, drop it on the detection mirror, and close the cover. Pay attention to prevent bubbles when covering the cover. Put the refractometer flat against the light source, adjust the eyepiece diopter circle so that the black and white dividing line of the field of view is clearly visible, and read the scale reading, which is the soluble solid content in the sample liquid, expressed as mass fraction (%). The test results are as follows Fig.13 shown.

[0141] from Fig.13 It can be seen that: with the increase of storage time, the soluble solids in the ethylene slow-release agent treatment group increased significantly compared with the CK group, the fruit sweetness increased, which is also a manifestation of fruit maturity, and high concentration of ethylene slow-release agent treatment can make the soluble solids of kiwifruit increase faster.

[0142] 7.3 Titratable Acid

[0143] The test method is: weigh 10.0g of evenly mixed fruit and vegetable samples (or absorb 10.0mL of juice), grind them in a mortar, transfer them to a 100mL volumetric flask, rinse the mortar with distilled water, transfer them to the volumetric flask, dilute to the scale, and shake well. Let it stand and filter. Absorb 20.0mL of filtrate, transfer it to a conical flask, add 2 drops of 1% phenolphthalein indicator, and titrate with a calibrated sodium hydroxide solution. Titrate until the solution begins to show pink and does not fade within 0.5 minutes. The endpoint is (pH = 8.1 ~ 8.3), record the amount of sodium hydroxide titrant used, and repeat three times. Then use distilled water instead of the filtrate for titration as a blank control. The test results are as follows Fig.14 shown.

[0144] from Fig.14 It can be seen that the titratable acid content of the ethylene slow-release agent treatment was significantly lower than that of the CK group, the sugar-acid ratio of the fruit increased, and the taste quality of the fruit improved, which is a sign that the fruit is ripe and reaches the edible period. In addition, high concentration of ethylene slow-release agent can make the titratable acid content decrease faster.

[0145] 7.4 Ethylene release

[0146] The test method is: Shimadzu gas chromatograph GC 2010-Pro hydrogen flame ionization detector (FID), carrier gas N2 flow rate 18mL / min, fuel gas H2 flow rate 21mL / min, combustion gas air flow rate 150mL / min. Injector temperature 120℃, chromatographic column temperature 60℃, detector temperature 200℃.

[0147] Open the sample container, place it upside down or use a fan to blow air to balance the gas in the container with the air. Then put about 1 kg of fruit on it and seal it for 1 hour at room temperature. Use a syringe to take 1.0 mL of gas from the gas outlet of the rubber stopper of the container, and inject it into the gas chromatograph for measurement. After the chromatograph is tested, the chromatogram is obtained. After loading the standard curve (area external standard method), the ethylene concentration of the injected gas can be obtained through microcomputer processing. The test results are as follows: Fig.15 shown.

[0148] from Fig.15 It can be seen that the ethylene slow-release agent treatment group can accelerate the ethylene release peak of the fruit compared with the CK group. The fruit ethylene release peak is also a sign of fruit maturity, indicating that the fruit has reached the optimal maturity node.

[0149] Test 8: Swelling capacity

[0150] Test samples: the ethylene slow-release material of Example 1, the ethylene slow-release material of Example 2, the ethylene slow-release material of Comparative Example 3 and the ethylene slow-release material of Comparative Example 4, therefore recorded as 350H, 700H, 350 and 700.

[0151] Test method: Weigh 1g of the above samples, add excess distilled water and let stand for 6 hours to fully absorb water and swell. Measure the mass of the product and determine its swelling rate after water absorption. The results are as follows: Fig.16 shown.

[0152] See also Fig.16 The addition of HACC improves the swelling capacity of the material, and the lower the ethephon concentration, the higher the swelling capacity. This is because the pH of the ethephon solution in Example 1 is less than 4 and is in a relatively stable state, so its swelling capacity is relatively low.

[0153] Experiment 9: X-ray diffraction measurement

[0154] X-ray diffraction is a major method for studying the phase and crystal structure of a substance. By performing X-ray diffraction on a material and analyzing its diffraction pattern, we can obtain information such as the composition of the material, the structure or morphology of the atoms or molecules inside the material, etc.

[0155] Test samples: the ethylene slow-release material of Example 1, the ethylene slow-release material of Example 2, the ethylene slow-release material of Comparative Example 3 and the ethylene slow-release material of Comparative Example 4, therefore recorded as 350H, 700H, 350 and 700.

[0156] This experiment also set up a CK group: the ethylene sustained-release material includes chitosan quaternary ammonium salt (HACC), sodium alginate, calcium chloride and porous starch. The mass ratio of each raw material and the preparation method refer to Example 1.

[0157] The measurement conditions are: Cu-Kα ray, voltage 40kV, current 40mA, scanning step length 0.02°, speed 0.2° / min, and measurement angle: 4°~30°. The results are as follows Fig.17 shown.

[0158] See also Fig.17 The starch crystal structure can be divided into four types: A-type, B-type, C-type and V-type. Analysis of the X-ray diffraction pattern shows that, except for the CK group, the other four groups of materials have characteristic peaks at 15°, 17°, 18° and 23°. The porous starch inside the material is a typical A-type starch, and the internal structure of this starch is more compact. The CK group material has no obvious crystallinity, indicating that the sodium alginate aqueous solution can hydrolyze the crystalline region of starch, and the addition of ethephon can enhance the crystallinity of the porous starch inside the material. The combination of ethephon and other materials inside the material is physical combination. Ethephon does not exist in the form of crystals inside the material. Because it is very easy to deliquesce in the air, it is difficult to completely remove the moisture during the preparation process. Chitosan quaternary ammonium salt has good solubility and is not easy to crystallize. There is a very weak diffraction peak at 26.7° at the 2θ angle, which is calcium alginate crystal. The addition of chitosan quaternary ammonium salt weakens the intensity of the diffraction peak, indicating that chitosan quaternary ammonium salt chemically combines with sodium alginate on the surface of the beads, reducing the crystallinity of calcium alginate. The comprehensive results show that ethephon does not chemically combine with other molecules inside the material, its structure remains intact, and can be well wrapped by the SA-PS complex. Ethephon does not exist in a crystalline form, which can help ethephon decompose after continuous moisture absorption.

[0159] Test 10: Determination of sustained release of materials under different humidity environments.

[0160] In this experiment, the addition amounts of porous starch (PS) and sodium alginate (SA) were changed, and the other addition amounts were the same as in Example 1, as shown in the following table.

[0161]

[0162]

[0163] In the above table: SA1, SA1.5 and SA2 respectively indicate that the added mass of sodium alginate is 1 g, 1.5 g and 2 g; PS5, PS10 and PS15 respectively indicate that the added mass of porous starch is 5 g, 10 g and 15 g; 100 ml is the volume of water.

[0164] According to the addition amounts of porous starch (PS) and sodium alginate (SA) in the above table, the addition amounts of other raw materials refer to Example 1, and the preparation method of Example 1 is used to prepare the corresponding ethylene sustained-release material samples for testing.

[0165] The test method is: take 3g of sample and place it in a sample bottle with a gas extraction port on the bottle cap, open the bottle cap and place it in an environment with a relative humidity of 15%, 50%, and 85% and a temperature of 21°C for 12 hours, then use a fan to blow out the residual ethylene gas in the bottle, tighten the bottle cap, and place it for 1 hour to collect ethylene gas. Finally, inject 1ml into Shimadzu gas chromatograph (Shimadzu gas chromatograph GC 2010-Pro hydrogen flame ionization detector (FID), carrier gas N2 flow rate 18mL / min, fuel gas H2 flow rate 21mL / min, combustion gas air flow rate 150mL / min. Injector temperature 120°C, chromatographic column temperature 60°C, detector temperature 200°C), obtain the peak area, and obtain the concentration of ethylene gas in the bottle based on the peak area and the ethylene gas standard curve, and obtain the ethylene release per gram of material per minute. Unit: (μL / g﹒min); the test results under different humidity are as follows Fig.18 shown.

[0166] See also Fig.18 , with the increase of sodium alginate content, its sustained release rate increased significantly; the increase of porous starch content had no significant effect on the ethylene sustained release rate. In addition, with the increase of ambient humidity, the ethylene release rates of the six materials increased significantly, and the ambient humidity was positively correlated with the ethylene release rate, but the correlation did not completely conform to the direct proportional function, but there was an inflection point. When the relative humidity of the environment was 15% RH and 50% RH, the ethylene release rate of the ethylene sustained-release material was very small and gentle, basically lower than 0.2μL / g﹒ min, and once the ambient humidity increased to 85% RH, the ethylene sustained-release rate of the ethylene sustained-release material increased significantly, up to 1.34μL / g﹒ min. It shows that the ethylene sustained-release material provided by the present invention is a humidity-sensitive material, and the ambient humidity should be adjusted to be close to 85% during the specific application process.

[0167] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An ethylene sustained-release material, characterized in that: The ethylene sustained-release material comprises chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate; the mass ratio of the chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate is (0.3-0.6):(0.01-0.15):(8-12):(7-15):

1.

2. The ethylene sustained-release material according to claim 1, characterized in that: The mass ratio of the chitosan quaternary ammonium salt, ethephon solution, porous starch, calcium chloride and sodium alginate is 0.5: (0.06-0.12): 10:11:1。 3. The method for preparing the ethylene sustained-release material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1. Prepare chitosan quaternary ammonium salt, ethephon, porous starch, calcium chloride and sodium alginate according to the mass ratio; S2, dissolving calcium chloride in water, adding chitosan quaternary ammonium salt, and subjecting to ultrasonication and stirring to obtain a mixed solution A; S3, dissolving ethephon in water to obtain an ethephon solution, and then dissolving sodium alginate in the ethephon solution until it is completely dissolved to form a stable and uniform system; then adding porous starch, homogenizing and degassing to obtain a mixed solution B; S4. Add the mixed solution B to the mixed solution A at a uniform speed, stir evenly, let stand, separate, obtain gel beads, and dry to obtain the granular target product.

4. The method for preparing the ethylene sustained-release material according to claim 3, characterized in that: In step S2, the frequency of ultrasound is 100 Hz to 160 Hz, and the time of ultrasound is 5 min to 10 min; the speed of stirring is 2000 r / min to 2200 r / min, and the time of stirring is 15 min to 25 min.

5. The method for preparing the ethylene sustained-release material according to claim 3, characterized in that: In the step S4, the standing time is 3 to 5 minutes, and the drying is performed at 55° C. to 70° C. for 7 to 8 hours.

6. The method for preparing the ethylene sustained-release material according to claim 3, characterized in that: The target product diameter is 3mm to 5mm.

7. Use of the ethylene slow-release material according to claim 1 or 2 in delaying the ethylene release rate.

8. Use of the ethylene slow-release material according to claim 1 or 2 in the controllable ripening of kiwi fruit.

Citation Information

Patent Citations

  • Preparation and application of ethephon controllable sustained-release material

    CN104145987A